HOW TO ORGANIZE A PERFECT READING LESSON (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2025)
This article explores the essential components of a perfect reading lesson in the context of teaching English as a foreign language. It examines theoretical foundations of reading instruction, identifies key stages that contribute to learners’ comprehension, and analyzes teacher strategies that create an engaging, effective, and student-centered learning environment. The study also highlights the importance of learner autonomy, motivation, and scaffolding in designing reading lessons. Practical recommendations and classroom applications are provided to guide teachers in implementing a well-structured reading lesson that develops both linguistic and cognitive skills.